THE ROLE OF EDUCATIONAL GAMES IN FACILITATING UNDERSTANDING OF BIOLOGICAL CONCEPTS IN EARLY CHILDHOOD - Cartono Cartono (Jurnal Scientia, 2022)
Early childhood between 4 and 6 years is known as pre-school age which experts call the golden age, because intelligence during this period increases by 50%. There are many ways that can be done for premature children. One of them is playing. Learning while playing or playing while learning can be fun and entertaining for children, including educational games to provide an understanding of Biology learning concepts. This research aims to explore and analyze the role of educational games in increasing understanding of biological concepts in early childhood. This research uses a qualitative approach with descriptive methods. This research shows that the use of educational game tools specifically for early childhood provides positive results. These play equipment, which are designed according to the child's age, have succeeded in improving sensory skills, helping children recognize their surroundings, and developing children's thinking abilities. Group play also helps children learn together, while the use of language in play supports the development of speaking skills. Apart from that, educational games can foster children's interest in science, especially biology, in an interesting and fun way. This research shows that educational games are not only a learning tool, but also an effective means of forming the basis for children's understanding of biological concepts.